STUDI EFEKTIVITAS DAN EFEK SAMPING FAVIPIRAVIR PADA PASIEN COVID-19 PNEUMONIA DI RUMAH SAKIT BHAYANGKARA SURABAYA - Rika Yulia; Fauna Herawati; Klara Rosjuita Hima; Ruddy Hartono; Puri Safitri Hanum (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Favipiravir's indication extended for COVID-19 disease. This background consideration is related to its mechanism of action or effectivity in some COVID-19 patients, with or without pneumonia. This research is a retrospective observational study and analysis descriptively. The research material is medical records of patients with COVID-19 pneumonia using favipiravir from December 2020-May 2021. A total of 33 samples obtained met the inclusion and exclusion criteria. Effectiveness was analyzed by calculating the percentage of COVID-19 pneumonia patients who only used favipiravir while they were being treated until the patient was discharged. The side effects were the number of COVID-19 patients who drug injury liver disease (AST and ALT increase more than three times upper limit) and neutrophenia. This study reported that favipiravir was effective in COVID-19 patients with pneumonia, seen from 78.79% of patients who only used favipiravir during treatment. There were no patients who had an increase in AST ALT >3×upper limit of normal, and only seven patients with neutropenia.